Personalized fluid and fuel intake for performance optimization in the heat - Cheuvront, S. N.; Kenefick, R. W. (Journal of Science and Medicine in Sport, 2021)
It is well appreciated that a loss of body water (dehydration) can impair endurance performance and that the effect is magnified by environmental heat stress. A majority of professional sports medicine and nutrition organizations recommend drinking during exercise to replace sweat losses and prevent dehydration, while also avoiding frank over-hydration. Knowledge of sweating rate, which is highest in the heat for any given metabolic rate, is therefore considered key to developing a sound drinking strategy. Exercise duration and the provision of liquid fuel interacts with required drink volumes in important ways that are infrequently discussed but are of utmost practical concern. This review details some challenges related to the optimized coupling of fluid and fuel needs during prolonged exercise in the heat and the need for personalization.